Treatment processes to eliminate potential environmental hazards and restore agronomic value of sewage sludge: A review. (15th January 2022) - Hoang, Son A.; Bolan, Nanthi; Madhubashani, A.M.P.; Vithanage, Meththika; Perera, Vishma; Wijesekara, Hasintha; Wang, Hailong; Srivastava, Prashant; Kirkham, M.B.; Mickan, Bede S.; Rinklebe, Jörg; Siddique, Kadambot H.M.
Abstract: Land application of sewage sludge is increasingly used as an alternative to landfilling and incineration owing to a considerable content of carbon and essential plant nutrients in sewage sludge. However, the presence of chemical and biological contaminants in sewage sludge poses potential dangers; therefore, sewage sludge must be suitably treated before being applied to soils. The most common methods include anaerobic digestion, aerobic composting, lime stabilization, incineration, and pyrolysis. These methods aim at stabilizing sewage sludge, to eliminate its potential environmental pollution and restore its agronomic value. To achieve best results on land, a comprehensive understanding of the transformation of organic matter, nutrients, and contaminants during these sewage-sludge treatments is essential; however, this information is still lacking. This review aims to fill this knowledge gap by presenting various approaches to treat sewage sludge, transformation processes of some major nutrients and pollutants during treatment, and potential impacts on soils. Despite these treatments, overtime there are still some potential risks of land application of treated sewage sludge. Potentially toxic substances remain the main concern regarding the reuse of treated sewage sludge on land. Therefore, further treatment may be applied, and long-term field studies are warranted, to prevent possible adverse effects of treated sewage sludge on the ecosystem and human health and enable its land application. Graphical abstract: Image 1 Highlights: Land application is one of the main disposal strategies for sewage sludge. Pollutants and pathogens in sewage sludge cause potential environmental pollution. Various treatments are applied to sewage sludge to enhance its land applicability. Nutrients and pollutants in sewage sludge are transformed during the treatments. Long-term field studies on the application of treated sewage sludge are warranted.